1983
DOI: 10.1111/j.1432-1033.1983.tb07687.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐reactivity of the selenoenzyme glutathione peroxidase with enzymatically hydroperoxidized phospholipids

Abstract: Selenium‐containing glutathione peroxidase (EC 1.11.1.9) was purified 6000‐fold from bovine red blood cells to apparent homogeneity. Lipoxygenase (EC 1.13.11.12) was enriched 20‐fold from soybean acetone powder. Linoleic acid was peroxidized with lipoxygenase and then used as a substrate in the glutathione peroxidase reaction. Analogous experiments were conducted with synthetic 1,2‐dilinoleoyl‐l‐α‐glycerophosphocholine and with natural bovine heart cardiolipin. The peroxidized phospholipids were reactive with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(41 citation statements)
references
References 34 publications
1
36
1
3
Order By: Relevance
“…The seleniumdependent GSH peroxidase does not appear to be involved, because addition of this enzyme did not show a detectable effect. Ths is in agreement with recent findings [26], ruling out the activity of this enzyme with enzymatically generated hydroperoxidized phospholipids as substrate, as long as there is no phospholipase present. We suggest the involvement of the phosholipid hydroperoxide glutathione peroxidase [15].…”
Section: The Ejject Of Thiolssupporting
confidence: 81%
“…The seleniumdependent GSH peroxidase does not appear to be involved, because addition of this enzyme did not show a detectable effect. Ths is in agreement with recent findings [26], ruling out the activity of this enzyme with enzymatically generated hydroperoxidized phospholipids as substrate, as long as there is no phospholipase present. We suggest the involvement of the phosholipid hydroperoxide glutathione peroxidase [15].…”
Section: The Ejject Of Thiolssupporting
confidence: 81%
“…For example, in the case of lipids it has been shown that both Se-dependent GSH peroxidase and GSH transferase isoenzymes inhibit microsomal lipid peroxidation [7], the substrates in both cases being free fatty acid hydroperoxides rapidly released from peroxidized phospholipids by phospholipase Az [7,8]. A recent study with GSH transferase isoenzymes shows that they differ considerably in tiaeir ability to utilize fatty acid hydroperoxides as substrates and that their ability to inhibit lipid peroxidation is proportional to their enzymic activity [9], In the case of DNA, 2/-radiation of aqueous solutions gives rise to pyrimidine hydroperoxide moieties [10] and incubation of peroxidized DNA or thymine hydroperoxide with GHS and rat liver soluble supernatant fraction causes oxidation of GSH implying that these peroxides are substrates for GSH peroxidase activity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen centred free radicals peroxidize both cellular lipids and DNA [1][2][3][4]: this damage appears to be mitigated by GSH-dependent enzymes [5][6][7][8]. For example, in the case of lipids it has been shown that both Se-dependent GSH peroxidase and GSH transferase isoenzymes inhibit microsomal lipid peroxidation [7], the substrates in both cases being free fatty acid hydroperoxides rapidly released from peroxidized phospholipids by phospholipase Az [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Preferential hydrolysis of oxidized fatty acids was demonstrated in isolated cell membranes and artificial membrane preparations, having been documented for cellular, digestive, and venom PLases. 25,[41][42][43] However, it should be noted that intact fatty acyl chains as well as possibly peroxidized fatty acyl chains of endogenous PE were hydrolyzed under the present conditions. PLase A 2 activity can be modified depending on the integrity of membrane phospholipids.…”
Section: Discussionmentioning
confidence: 96%